(untitled) (Bangladesh Journal of Nuclear Medicine, 2015)
Patients with follicular carcinoma of thyroid may have asymptomatic involvement of adrenal gland and associated metastases to other organs, which may remain undetected for long time if not diagnosed, treated and followed up properly. A very rare case of adrenal metastasis from follicular carcinoma of thyroid, five years after total thyroidectomy is presented. The patient also had synchronous involvement of bones including an unusual site in upper end of left tibia. Here, emphasis is given on awareness of the possibility of unique metastatic deposits of follicular carcinoma of thyroid at unexpected sites as this has a significant impact on clinical decision-making and prognosis of the patients. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22499 Bangladesh J. Nuclear Med. 17(1): 97-103, January 2014